Early Linguistic Markers of Trauma-Specific Processing Predict Post-trauma Adjustment - Kleim, Birgit; Horn, Andrea B.; Kraehenmann, Rainer; Mehl, Matthias R.; Ehlers, Anke (Frontiers in Psychiatry, 2018)
Background: Identifying early predictors for psychological disorders, such as posttraumatic stress disorder (PTSD), is crucial for effective treatment and prevention efforts. Obtaining such predictors is challenging and methodologically limited, for example by individuals' distress, arousal and reduced introspective ability. In this study, we investigated the predictive power of language-based behavioral markers of psychological processes. Methods: Markers were derived from computerized text-analysis of trauma and control narratives provided by N= 163 trauma survivors within 18 days post-trauma. PTSD symptoms and self-reports of trauma related processes were assessed, with follow up of symptom assessment 6 months later. Results: Trauma narratives with more cognitive processing words (indicating more cognitive elaboration), fewer death-related words (indicating perceived threat to life or mental defeat), and fewer first-person singular pronouns (indicating self-immersed processing) were associated with PTSD symptoms at 6 months after trauma. These effects were specific to trauma narratives and held after controlling for early PTSD symptom severity and verbal intelligence. When self-report questionnaires of related processes were considered together with the trauma narrative linguistic predictors, use of first-person singular pronouns remained a significant predictor alongside self-reported mental defeat. Conclusions: Language-based processing markers are early predictors and can serve as vulnerability indicator for later chronic PTSD that may complement questionnaire measures in forecasting resilience and post-trauma adjustment.